Reproduction of the non-native fish Lepomis gibbosus (Perciformes: Centrarchidae) in Brazil - Rangel E. Santos; Tayara P. Silva; Igor V. Chehayeb; André L. B. de Magalhães (Revista de Biología Tropical, 2012)
Minas Gerais is the fourth largest Brazilian state, and has an estimate of 354 native fish species. However, these fish species may be threatened, as this state has the highest rank of fish introductions reported for Brazil and South America. As one from the total of 85 non-native species detected, Lepomis gibbosus was introduced in the 60s to serve both as foragefish and to improve sport fishing. In this study, we evaluated the establishment of L. gibbosus in a shallow lake in the city of Ouro Preto, Doce River basin, state of Minas Gerais, Southeastern Brazil. We collected fish with fishing rods every two months from March 2002-February 2003. Fragments of gonads from a total of 226 females and 226 males were obtained and processed following standard histological techniques; then 5-7μm thickness sections were taken and stained in hematoxylin-eosin. Besides, for each specimen, the biometric measurements included the standard length (SL) and body weight (BW); and the sex ratio was obtained. The reproductive cycle stages were confirmed by the distribution of oocytes and spermatogenic cells. The type of spawning was determined by the frequency distribution of the reproductive cycle stages and ovarian histology. Based on the microscopic characteristics of the gonads, the following stages of the reproductive cycle were determined: one=Rest, two=Mature, three=Spawned for females or Spent for males; males and females in reproduction were found throughout the study period. Post-spawned ovaries containing oocytes in stages one (initial perinucleolar), two (advanced perinucleolar), three (pre-vitellogenic), four (vitellogenic) and post-ovulatory follicles indicated fractionated-type spawning in this species. The smallest breeding male and female measured were 4.6 and 4.9cm standard length, respectively, suggesting stunting. The sex ratio did not vary between males and females along the year and bimonthly, being 1:1. Moreover, L. gibbosus appears to be at stage three of biological invasion: establishment through reproduction. We suggest to deliver information about “non-native species” through lectures in schools, colleges/ universities, NGOs, government and environmental agencies in the cities and villages, in order to try to prevent environmental degradation by the introduction of non-native fish such as L. gibbosus in the region. We also recommend high fines for redhanded, and the import ban of non-native fish species to the region.